2022
DOI: 10.3389/fvets.2022.935133
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association studies for the identification of cattle susceptible and resilient to paratuberculosis

Abstract: Mycobacterium avium subsp. paratuberculosis (MAP) causes Johne's disease or paratuberculosis (PTB), with important animal health and economic implications. There are no therapeutic strategies to control this disease, and vaccination with inactivated vaccines is limited in many countries because it can interfere with the intradermal test used for bovine tuberculosis detection. Thus, infected animals either get culled after a positive ELISA or fecal PCR result or die due to clinical disease. In this study, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Current control strategies focus on preventing the transmission of MAP through management practices ( Barkema et al., 2018 ) by testing and culling positive animals, decreasing the incidence of new infections, preventing spread, and protecting negative herds, and decreasing prevalence in bulk tank milk ( Wolf et al., 2014 ). Identifying and selectively breeding cattle with natural resistance to MAP infection is also an approach recently employed by Canada and some European countries ( Alonso-Hearn et al., 2022 ; Sanchez et al., 2022 ). Despite considerable efforts to control Johne's disease, their effectiveness has been limited mostly due to high costs, suboptimal diagnostics, and incomplete knowledge of MAP pathogenesis ( Nielsen and Toft, 2006 ; Nielsen and Toft, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Current control strategies focus on preventing the transmission of MAP through management practices ( Barkema et al., 2018 ) by testing and culling positive animals, decreasing the incidence of new infections, preventing spread, and protecting negative herds, and decreasing prevalence in bulk tank milk ( Wolf et al., 2014 ). Identifying and selectively breeding cattle with natural resistance to MAP infection is also an approach recently employed by Canada and some European countries ( Alonso-Hearn et al., 2022 ; Sanchez et al., 2022 ). Despite considerable efforts to control Johne's disease, their effectiveness has been limited mostly due to high costs, suboptimal diagnostics, and incomplete knowledge of MAP pathogenesis ( Nielsen and Toft, 2006 ; Nielsen and Toft, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is not any effective therapeutic treatment to cure bovine PTB and the parenteral vaccination with heat-killed inactivated vaccines is not widely accepted by animal health authorities on the grounds of a slight interference with the diagnosis of bovine tuberculosis (Garrido et al, 2013 13 ). The identi cation and selection of animals naturally less susceptible to MAP infection or with increased resistance to PTB is important for disease control and breeding purposes (Alonso-Hearn et al, 2022 14 ). Genome-wide association studies (GWAS) have allowed the identi cation of single-nucleotide polymorphisms (SNPs) associated with PTB susceptibility and tolerance using whole-genome sequence (WGS) (Canive et al, 2021a 15 ; Canive et al, 2021b 16 ; Canive et al, 2022a 17 , Alonso-Hearn et al, 2022 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The identi cation and selection of animals naturally less susceptible to MAP infection or with increased resistance to PTB is important for disease control and breeding purposes (Alonso-Hearn et al, 2022 14 ). Genome-wide association studies (GWAS) have allowed the identi cation of single-nucleotide polymorphisms (SNPs) associated with PTB susceptibility and tolerance using whole-genome sequence (WGS) (Canive et al, 2021a 15 ; Canive et al, 2021b 16 ; Canive et al, 2022a 17 , Alonso-Hearn et al, 2022 14 ). However, interpreting the biological mechanisms behind these SNPs remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that host genetics governs variations in susceptibility to MAP infection, and therefore selective breeding could decrease the susceptibility to MAP infection [ 13 ]. In recent years, genome-wide association studies (GWAS) have identified single nucleotide polymorphisms (SNPs) associated with susceptibility to MAP infection [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%